New Insights on Basic and Clinical Aspects of EEG and MEG Connectome - Jing Xiang (Frontiers Research Topics, 2018)
Recent advances in the neuroimaging field areas allow us to visualize the aggregate of neural connections at the macroscopic level within the brain, the so-called "connectome". In order to promote the development of the neurophysiological investigation of connectome of brain oscillations, this eBook aims at bringing together contributions from researchers in basic and clinical neuroscience using EEG and MEG connectome analysis. The most important focal point will be to address the functional roles of connectome of brain oscillations in contributing to understandings of higher cognitive processes in normal subjects and pathophysiology of psychiatric diseases. This Research Topic presented novel methodologies and various applications of neurophysiological connectome analysis. As a result, these papers were cited more than 120 times in these four years in total and threw light and impact on new directions for investigating the connectome of human brain.